1985
DOI: 10.1159/000183338
|View full text |Cite
|
Sign up to set email alerts
|

Acetate versus Lactate in Peritoneal Dialysis Solutions

Abstract: The acid-base characteristics of two peritoneal dialysis solutions containing either lactate or acetate are compared and the time course of changes in intraperitoneal pH following instillation into the abdominal cavity is measured. The concentration of titratable acid (cTA) is 5.58 mmol/l or 7 times as high in solutions containing acetate as in those containing lactate (0.79 mmol/l). The buffer capacity, -dcTA/dpH, is 11.43 and 1.82 mmol/l, respectively. Following intraperitoneal instillation of 1.5 liter of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…For example, it has been reported that abdominal pain occurs in 78% of patients during an episode of peritonitis [4]. However, pain experienced during intraperitoneal infusion of the dialysis solution also occurs in the non-peritonitis state, and is distinguished by the abdominal pain appearing within the first minute or so after starting infusion of the PD solution, but which generally diminishes during the dwell [5]. Infusion pain is usually observed in new patients commencing dialysis and is often transient in nature, spontaneously disappearing over time [3,6].…”
mentioning
confidence: 99%
“…For example, it has been reported that abdominal pain occurs in 78% of patients during an episode of peritonitis [4]. However, pain experienced during intraperitoneal infusion of the dialysis solution also occurs in the non-peritonitis state, and is distinguished by the abdominal pain appearing within the first minute or so after starting infusion of the PD solution, but which generally diminishes during the dwell [5]. Infusion pain is usually observed in new patients commencing dialysis and is often transient in nature, spontaneously disappearing over time [3,6].…”
mentioning
confidence: 99%
“…From in vivo experiments, it is known that the pH of PDFs is neutralized within a few minutes [33]. During this short window, however, the low pH that is inherent in conventional, one compartment, lactate-based PDFs may adversely affect mesothelial cells, by the lowering of intracellular pH and impairment of metabolism due to changed redox potentials [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike the results of the in vitro studies, pH is not a major factor in the in vivo setting. Such a discrepancy is due to the fact that an acidic PDF is pH neutralized within 30 min after exposure to the peritoneal cavity [6, 7, 8]. It demonstrates that although pH can be a major factor that affects viability of cells in vitro, it does not affect them in vivo because of their biological buffering ability.…”
Section: Discussionmentioning
confidence: 99%
“…The acidic PD solution is neutralized within 30 min after being instilled into the abdominal cavity due to the large buffering capacity of the peritoneal membrane and of the intraperitoneal residual fluid [6, 7, 8]. It has been reported that an acidic pH has deleterious impacts on the host defense in the abdominal cavity and on the mesothelial cells [9, 10].…”
Section: Introductionmentioning
confidence: 99%